Photography as a visual literacy Tool - Caicedo Barreto, Sandra Liliana (Colombian Applied Linguistics Journal, 2006)
This article is an attempt to show some theoretical issues founded on how visual literacy processes come about through a photography project. The framework explained is based on Wendy Ewald’s literacy through photography study (LTP), and on Freire’s reading conception which stare at literacy as a process for social inclusion. Further a literature review, I provide some practical aspects based on a visual literacy experience carried out in a private school in Bogotá. Likewise, I describe some key moments of the visual literacy process that can be developed by an image’s viewer. All this process is based on the socio cultural perspective.